(untitled) (Boletín Semillero de Investigación en Familia, 2022)
Introduction: Suicide is the deliberate act of taking one’s own life with explicit or implicit evidence that it was self-inflicted and with the intention of causing one’s own death. It is a public health problem due to the impact it generates on families and societies, due to the loss of many years of life that could have been lived. Objective: to strengthen the knowledge of the teachers of the Francisco José de Caldas Educational Institution in the management of self-harm and suicide. Materials and methods: an educational workshop was carried out based on the course Prevention of self-harm and suicide: empowerment of primary health care professionals of the Pan American Health Organization (PAHO), aimed at teachers of the Educational Institution Francisco Jose de Caldas de Villavicencio. Results: 57 10th and 11th grade teachers, from the institution’s morning and afternoon sessions, between 35 and 60 years of age, with a predominance of females, participated. Conclusion: mental health is an important factor of direct influence on the quality of life of adolescents, consequently, it is essential to strengthen the knowledge of teachers in the identification of warning signs and the prevention of injuries in students.